Estudo e Definição de uma Metodologia de Teste de Software no Contexto de Sistemas Embarcados Críticos - BARBOSA, Jacson Rodrigues (2011)
Computing is becoming increasingly critical in the embedded applications space and depending on the software, its malfunction may result in a severe financial loss to the loss of human life. Considering this scenario, we presented a systematic literature review in order to investigate the evolution of work-related activity test critical embedded software in order to evaluate the level of compliance found in the work to the standard DO- 178B (Software Considerations in Airborne Systems and Equipment Certification). This research, in addition to conducting a systematic review of publications about this issue, has resulted in the composition of primary studies to define a process of quality testing and including the requirements of DO-178B at their different levels of criticality.